Antithrombin III Geneva: A Hereditary Abnormal AT III with Defective Heparin Cofactor Activity - de Moerloose, P A; Reber, G; Vernet, Ph; Minazio, Ph; Bouvier, C A (Thrombosis and Haemostasis, 1987)
A 43-year-old man presented a pulmonary embolism. The unusual circumstances of apparition, the age and the increased heparin requirements suggested an antithrombin III (AT III) deficiency. AT III activity was low in the propositus and seven other members of his family (mean 55%), but immunologic levels were normal (mean 110%). Crossed immunoelectrophoresis in absence of heparin showed a normal pattern, but in presence of heparin showed an abnormal peak as compared with controls. Kinetics experiments showed a normal inhibition of thrombin and Xa in absence of heparin, but abnormal in presence of heparin. Affinity chromatography on heparin-Sepharose revealed two populations of AT III, one of which was devoid of heparin cofactor activity. The toponym AT III Geneva is proposed for this new familial abnormal AT III with defective heparin cofactor activity.
Keywords: Antithrombin III; Heparin cofactor